PENGARUH STRES KERJA DAN BEBAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN PADA PT SEPULSA TEKNOLOGI INDONESIA - Deidra Aisyah Fitri Prananti; Sugeng Suroso; Ery Teguh Prasetyo (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Sepulsa Teknologi Indonesia, as a company operating in the technology and information sector, is also not immune from these challenges. In an increasingly competitive context, PT. Sepulsa Teknologi Indonesia has a great interest in understanding the factors that can influence its employees' decisions to stay with the company or to resign. One factor that may play an important role in this is work stress and workload faced by employees. The aim of this research is to determine the effect of work stress and workload on employee turnover intention at PT Sepulsa Teknologi Indonesia. The type of research used is quantitative. The results obtained are that work stress is an individual's reaction to a mismatch between job demands and the resources they have, while workload refers to the volume and complexity of tasks carried out by employees. The majority of reasons why people stop working are because they resign, the workload is too high, causing work stress and getting a job offer in a new place. The conclusions obtained include that turnover intention which is influenced by work stress shows that H1 is accepted, turnover intention which is influenced by workload shows that H2 is rejected, and turnover intention which is influenced by stress and workload shows that H3 is accepted.